Climate change resilient strategies for greener Africa: The perspectives of energy efficiency and eco-complexities - Kingsley Ikechukwu Okere; Emmanuel Uche (Sustainable Futures)
The far-reaching effects of climate change on the environment are particularly pronounced in developing countries, with the African continent facing the highest risks. Ironically, there is a scarcity of empirical research addressing the perspectives of African nations regarding climate change mitigation strategies. In alignment with the ''African We Want'' agenda, this study investigates energy efficiency within the KAYA identity framework as a strategic pathway toward a greener Africa. The empirical findings, derived from feasible generalized least squares (FGLS) and panel-corrected standard errors (PCSE), indicate that Africa's current energy and carbon intensity profiles are detrimental to sustainable growth. The results reveal a heavy reliance on traditional energy sources rather than cleaner alternatives. The validation of the Environmental Kuznets Curve (EKC) hypothesis suggests that economic activities could contribute to cleaner environments in the long term. While eco-complexities and population growth are significant drivers of pollution, the role of ICT has shown substantial climate resilience effects. As a policy recommendation, the continent must reduce its dependence on traditional energy sources and shift towards more environmentally friendly modern energy options. Embracing modern manufacturing techniques and facilitating economic transformations will be crucial for achieving the continent's climate change resilience goals by 2060.